Membrane Topology of the Streptococcus pneumoniae FtsW Division Protein - Gérard, Philippe (American Society for Microbiology, 2002)
The topology of FtsW from Streptococcus pneumoniae, an essential membrane protein involved in bacterial cell division, was predicted by computational methods and probed by the alkaline phosphatase fusion and cysteine accessibility techniques. Consistent results were obtained for the seven N-terminal membrane-spanning segments. However, the results from alkaline phosphatase fusions did not confirm the hydropathy analysis of the C-terminal part of FtsW, whereas the accessibility of introduced cysteine residues was in agreement with the theoretical prediction. Based on the combined results, we propose the first topological model of FtsW, featuring 10 membrane-spanning segments, a large extracytoplasmic loop, and both N and C termini located in the cytoplasm.